Effects Of Aqueous-Ethanolic Extracts And Fractions Of Moringa Oleifera Lam. Leaf On Diabetic And Metabolic Syndrome Rats - Irfan, Hafiz Muhammad (2017)
Recent advancements in isolation and identification of active compounds present in medicinal plants have culminated in a fractionation-guided targeted approach in search of bioactivities. Thus, the present research was designed to determine the most active extract, active fraction and to identify active principle from Moringa oleifera leaf aqueous-ethanol extracts in diabetic rats. In addition, these extracts were also assessed in metabolic syndrome rats. Five different aqueous ethanol extracts (95, 75, 50, 25% [v/v] ethanol and 100% water) were orally tested in normoglycemic Sprague Dawley rats for anti-hyperglycemic activity and glucose tolerance.